2020
DOI: 10.1088/1757-899x/901/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Probability Concepts of Transfer Load to the Foundation of Container Structure

Abstract: This paper presents stochastic analysis using the perturbation method to model the structure of a container to verify the distributions of probability of maximum and minimum axial forces reactions in piles. The proposed simulation of a container port terminal under 11 scenarios of load combinations was presented. The probability distributions for live loads are assigned according to the input parameters of simulation data. Part of the load itself is implicitly combined such as vertical live load which includes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The variables were analyzed using the ordered response model, and the variables were not dependent on the characteristics of the road, which included straightness. It was found that greater force (both straight and curved) increases the injury's severity [14][15][16].…”
Section: Road Alignmentmentioning
confidence: 99%
“…The variables were analyzed using the ordered response model, and the variables were not dependent on the characteristics of the road, which included straightness. It was found that greater force (both straight and curved) increases the injury's severity [14][15][16].…”
Section: Road Alignmentmentioning
confidence: 99%